Description and Assessment of an Antimicrobial Substance from Marine Actinobacteria - Selvamani, V.; Senthilkumar, P. K.; Vigneshwari, J.; Janagakumar, S.; Dhivyadharshini, M. (UTTAR PRADESH JOURNAL OF ZOOLOGY, 2024)
Streptomyces is thought to be the primary source of bacteria for the synthesis of bioactive substances, such as naturally occurring antibiotics. Finding and identifying the actinomycetes exhibiting antagonistic activity was the primary goal of the current investigation. A strain of actinomycetes that was isolated from marine sand samples that were collected off the Indian coast of Vedharanyam exhibited antimicrobial activity against a number of microbial pathogens. The nutritional requirements and cultural conditions for maximal growth and yield of bioactive compounds have been optimized under shake flask condition. Analyze the compound characterization of the sample such as UV, FT-IR, GC-MS and sequencing 16S rRNA for species identification. The actinomycetes isolates which are isolated from sediment sample can be further used as antimicrobial activity agents against bacterial and fungal pathogens and their compound characterization.